TABOO IN BUGINESE LANGUAGE SPOKEN IN TANJUNG KARANG VILLAGE: A DESCRIPTIVE QUALITATIVE STUDY - Nursyafeizah, Andi; Budasi, I Gede; Putu Ramendra, Dewa (Jurnal Impresi Indonesia, 2024)
In Bugis culture, taboo language reflects the culture of Bugis society. This is part of the culture of the Bugis people, and the next generation really needs to understand these words. This research aims to identify taboo words, identify their forms, and analyze their references. This research was designed in the form of descriptive-qualitative research. This research was conducted in Tanjung Karang Village, Sebatik District, Nunukan Regency, North Kalimantan Province. Primary data in this research was collected using in-depth interview techniques. The researcher acts as the main instrument which is equipped with other instruments in the form of interview sheets. The data obtained was analyzed according to the research objectives. Taboo words, their forms and references were analyzed using the theories of Frazer (1955) and Montagu (1973). The research results show that the 45 taboo words can be grouped based on the use of taboo words about harmony with God (5 taboo words), the use of taboo words about harmony with humans (35 taboo words), and the use of taboo words about harmony with the environment (5 taboo words). Related to taboo in the form of 22 taboo names and taboo words, and 23 in the section on swear words, and related taboo references (12 references). Based on the list of taboo words above, it can be concluded that the term or name of taboo is often found and used in the Bugis language in the village of Tanjung Karang, especially in prohibitions which are called taboo in the sense that taboo is a word that when spoken contains magic, and prohibition. or an insult that makes someone offended if it is said.